Article Commentary: An Assistance-as-Needed Control Paradigm for Robot-Assisted Ankle Rehabilitation. (March 2014) - Zhang, Mingming; Davies, T. Claire; Nandakumar, Anoop; Xie, Shane
Robots have been developed for treatment and rehabilitation of ankle injuries. Two reviews have been conducted involving the effectiveness of robot-assisted ankle rehabilitation and ankle assessment techniques respectively to investigate what the optimal therapy is. This study proposes an assistance-as-needed (AAN) control paradigm for potential use in robot-assisted ankle rehabilitation based on the review results. This AAN control strategy will consider real-time ankle assessment and make rehabilitation more effective.